Influences of Corydalis decumbens on the Activities of CYP450 Enzymes in Rats with a Cocktail Approach. (21st January 2019) - Cheng, Chen; Qian, Jianchang; Wang, Zhe; Li, Wanshu; Huang, Chengke; Chen, Mengchun; Dong, Yaoyao; Lian, Lejing; Sun, Wei
Abstract : Corydalis decumbens, a Traditional Chinese Medicine, has been widely used for the alternative and/or complementary therapy of hypertension, arrhythmias rheumatoid arthritis, sciatica, stroke, hemiplegia, paraplegia, and vascular embolism. The aim of this study was to determinate the potential effects of Corydalis decumbens on the five cytochrome P450 (CYP) enzyme activities (CYP1A2, CYP3A4, CYP2C9, CYP2C19, and CYP2D6) by cocktail approach. To evaluate whether concurrent use of Corydalis decumbens interferes with the effect of several prescription drugs, saline (control group) or Corydalis decumbens (XTW group) were administrated via gavage for 7 successive days. A probe cocktail solution (phenacetin, omeprazole, metoprolol, tolbutamide, and midazolam) was given 24 h after the last dose of saline or Corydalis decumbens . A specific and sensitive UHPLC–MS/MS method was validated for the determination of five substrates and their metabolites in control group and XTW group. Our results indicated that Corydalis decumbens could have inductive effects of CYP2C19 and inhibit the activities of CYP1A2 and CYP3A4. However, Corydalis decumbens had no significant influence on CYP2C9 and CYP2D6. The herb-drug interaction should require more attention by careful monitoring and appropriate drug dosing adjustments to the concurrent use of western medications which were metabolized by CYP1A2, CYP2C19, and CYP3A4 in human— Corydalis decumbens, Cytochrome P450, Cocktail, Pharmacokinetics, herb–drug interactions.